Development and Evaluation of Clinical Decision Support for Immigrant Child Health Screening in Primary Care - Michel, Jeremy Joseph; Karavite, Dean; While, Daniel; Mudenge, Nadège; Dawson-Hahn, Elizabeth; Yun, Kate (Applied Clinical Informatics)
Background While Electronic Health Record (EHR)-based tools for refugee health screening exist, supports for other immigrant children has lagged. Reasons include lack of time, difficulty determining screening eligibility, and lack of awareness of screening recommendations. EHR-based tools to promote immigrant child health screening (ICHS) can address these challenges, but guidance is needed for tools that are usable by clinicians and acceptable to immigrant families. Objectives Develop useful EHR-based tools to support ICHS while incorporating evaluation of acceptability, usability, and implementation effort. Methods We followed a 5-step human-centered design approach to develop EHR-based tools for ICHS. This included: (1) Representative users completing semi-structured interviews. (2) Health professionals and community advisory groups providing ongoing guidance. (3) Developing a functional prototype. (4) Usability testing of the prototype. And (5) an assessment of implementation effort involving a second site installation coupled with expert implementation time-estimations. Results Sixteen interviewees discussed screening barriers and how EHR-based tools could support discussing nativity (country of birth). From the interview findings and in consultation with advisory group members, we developed an EHR-based toolkit including non-interruptive alerts, an order set, and documentation prompt. Ten clinicians completed usability testing. All recognized the alert and asked country of birth. Most (9) were satisfied with the system. All felt it was easy to use, helpful, and would not hinder patient care. Content experts (n=8) estimated installation times (range 4-20 hours, median 10) with high levels of confidence (range 1-5, median 4). A second-site test installation required 7.25 hours. Conclusion Our EHR-based tools designed with guidance of experts were highly rated on usability and can help clinicians identify patients eligible for ICHS in a sensitive manner. Installation testing demonstrated that this content could be implemented in a reasonable timeframe at external sites.